Cell-mediated immune response to bovine herpes virus (BHV-1) infection in experimental animals - Srinivasulu, T; Babu, T Suri; Rao, M V Subba (The Indian Journal of Animal Sciences, 2012)
Leucocyte migration inhibition (LMI) test was used to study the cell-mediated immune response in rabbits after experimental infection with BHV-1. The BHV-1 was propagated in MDBK cell line cultures with titre of 108.5 TCID50/ml and used for antigen preparation. The optimum concentration of antigen used was 100 Âµg/ml for LMIT. Rabbits (10) divided into 2 groups (A and B) of 5 each, including control were used. The peak LMI response was observed 30th day post infection (PI) with 62.90% migration inhibition in group A and 25th day PI in group B with 60.59% migration inhibition. The overall LMI response showed by the rabbits of group A was not significantly different (P>0.05) from the rabbits of group B. However, there was significant positive correlation (P